CHAT PDF Y SU CONTRIBUCIÓN EN EL APRENDIZAJE AUTÓNOMO DE LOS ESTUDIANTES DE LA FACULTAD DE CIENCIAS JIRÍDICAS, SOCIALES Y DE LA EDUACIÓN, EN EL PERIODO ACADÉMICO ABRIL – AGOSTO 2024 - SAN LUCAS MARISCAL MIRIAN LISETH (2024)
The analysis focuses on examining how PDF chat influences the independent learning of students at the Faculty of Legal, Social and Educational Sciences during the academic period between April and August 2024. A combined methodology is used that combines qualitative data and quantitative to fully understand the effect of this technological tool on the autonomous learning process of university students. Chat PDF, an interactive platform, facilitates communication between teachers and students and collaboration between colleagues. In addition, we also provide complementary materials, which are essential tools for the development of educational autonomy. The results indicate that the use of PDF Chat has a positive effect on promoting independent learning. An increase in student motivation and participation is observed, as well as an increase in their ability to be independent in their learning. It also facilitates collaboration and the exchange of ideas between colleagues. Chat PDF is a promising tool to promote autonomous learning in higher education, providing students with the resources and support they need to play an active role in their academic education. Keywords for this study include PDF chat, self-directed learning, law, social sciences, faculty of education, educational technology, peer collaboration, student motivation, educational resources, student engagement, self-management of learning, and teacher interaction. and students. it's included.